Reference values for thrombin dynamics in platelet rich plasma. (17th February 2021) - Yan, Qiuting; Ninivaggi, Marisa; de Laat, Bas; de Laat-Kremers, Romy M. W.
Abstract: Thrombin generation (TG) is a better determinant of the overall function of the hemostatic system than routinely used clotting time-based assays and can be studied more in detail by thrombin dynamics analysis. Platelet poor plasma is often used to measure TG, however, measuring the contribution of the platelets is also important as patients with a low platelet count or with dysfunctional platelets have an increased risk of developing bleeding. In this study, platelet rich plasma (PRP) was collected from 117 healthy individuals. PRP was measured undiluted and diluted to a varying platelet concentration of 10*10 9 /L to 400*10 9 /L. Prothrombin conversion and thrombin inactivation were calculated from the data obtained by the TG parameters and coagulation factor levels (antithrombin, α2 Macroglobulin (α2 M) and fibrinogen). Reference ranges of TG and thrombin dynamics in PRP of 117 healthy individuals were established. Peak, velocity index and the maximum rate of prothrombin conversion increased linearly with platelet count, but endogenous thrombin potential reached a maximum at 150*10 9 /L as seen in a subset population (n = 20). More extensive analysis revealed that a platelet count below 50*10 9 /L did not affect TG parameters (except for the ETP). Correlation analysis indicated that the platelet count mainly affected the rate of prothrombin conversion. Inhibition of thrombin by antithrombin and α2 M increased with increasing TG, but the ratio of inhibition by antithrombin or α2 M remained the same independently of the total thrombin formed. In conclusion, TG and thrombin dynamics were assessed in PRP of healthy donors to provide reference values for future TG studies in PRP. Increasing the platelet count mainly affected the rate of prothrombin conversion and TG, rather than the total amount of thrombin formed.